Peptide Biomaterials for Tissue Regeneration - Ross, Alex; Sauce-Guevara, Mildred A.; Alarcon, Emilio I.; Mendez-Rojas, Miguel A. (Frontiers in Bioengineering and Biotechnology, 2022)
Expanding the toolbox of therapeutic materials for soft tissue and organ repair has become a critical component of what we know as tissue engineering. While animal or plant derived proteins have been the foundation in developing biomimetic tissue constructs, using peptides as either constituents or frameworks for the materials has increasingly gained momentum in recent years. This mini review discusses recent advances in peptide-based biomaterials’ design and application. We also discuss some of the future challenges and opportunities that peptide-based structures pose to the field of tissue engineering and regenerative medicine.